THE DEVELOPMENT OF MATHEMATICS E-LKPD ASSISTED BY FLIPBOOK BASED ON DISCOVERY LEARNING TO IMPROVE STUDENTS’ LEARNING OUTCOMES - Novi Mayasari; Ari Indriani; Junarti Junarti; Puput Suriyah; Nellya Virza (JETL (Journal of Education, Teaching and Learning), 2025)
This study aims to develop an educational resource in the form of an electronic student worksheet (E-LKPD) supported by a flipbook and based on the Discovery Learning model, to improve students’ learning outcomes on the topic of plane figures at SMP Negeri 1 Rengel. The background to this research stems from the low mathematics achievement among students, attributed to limited interest in learning and the lack of interactive teaching media suited to students’ needs. The study adopts a Research and Development (R&D) approach, utilizing the 4-D development model (Define, Design, Develop, Disseminate), although it is implemented only up to the development stage. The instruments employed include expert validation sheets, practicality questionnaires, and learning outcome tests. The findings reveal that the developed E-LKPD falls into the categories of valid, practical, and effective for classroom use. The use of this flipbook-assisted E-LKPD based on Discovery Learning has been shown to significantly enhance students’ engagement, independence, and learning outcomes. Therefore, this teaching medium is considered suitable to be used as an alternative instructional resource in mathematics learning, contributing to the improvement of educational quality.